La fortuna de «Tirant lo Blanch» entre alguns lectors hispànics dels segles XVI al XIX - Mérida, Rafael M. (Caplletra. Revista Internacional de Filologia, 1997)
The author reviews the history of Tirant in the Iberian Peninsula through the literary tastes and reflections of characters who have a main importance in the creation of the Hispanic aesthetic canon: from the different translations to the critical and literary opinions. Mérida describes to us the possibilities of reading and the influences, possible or not, of Martorell’s work on other authors’ creations, such as Rodríguez de Montalvo, Cervantes or Avellaneda. From the aforementioned authors, to critics such as Clemencín or Pascual de Gayangos, Mérida has presented a study which becomes the testimony of the life and death of the experts’ fascination of Martorell’ s great novel.